A new approach to identifying high-tech manufacturing SMEs with sustainable technological development : Empirical evidence - Pylaeva, Irina S.; Podshivalova, Mariya V.; Alola, Andrew Adewale; Podshivalov, Dmitrii V.; Demin, Alexander A. (Elsevier, 2022)
Industry 4.0 has already become part of the world's largest manufacturers and is beginning to influencing small and medium-sized enterprises (SMEs) through the supply chain. High-tech industries, such as pharmaceuticals, electronic equipment, aircraft manufacturing, etc., will be the first to face technological transformation. To this end, it becomes relevant to assess the sustainability of the technological development of SMEs as a factor of their successful digital transformation. This paper fills a gap in the study of such development as it pertains to Russian high-tech SMEs. Based on a critical literature review, we propose a new approach to assessing the sustainable technological development of these industries. The approach is distinguished by the use of a set of five indicators highlighted during the literature review, which can be quantified based on financial statements. The choice of variables is justified by their compliance with the specifics of industrial SMEs and KMO and Bartlett tests. We empirically tested the selected indicators using a sample of 7980 enterprises in two high-tech industries: Electrical and Electronic Equipment (EEE). We concluded that the larger the business, the higher the sustainability of its technological development. At the same time, SMEs have two key advantages in the implementation of technological development – a decrease in resource costs of production, flexibility in asset management and gross profit. The proposed approach allows us to identify promising high-tech SMEs for the transition to Industry 4.0 technologies. Our research will be useful both for private enterprises when searching for technologically promising contractors and for public authorities when analyzing and selecting enterprises for pilot digital transformation.
Keywords: Manufacturing SMEs; Electrical and Electronic equipment (EEE); High-tech industry; High-tech SMEs; technological development; sustainable development; fi=Taloustiede|en=Economics|